Assignment of the vibrations of the S0, S1, and D+0 states of perhydrogenated and perdeuterated isotopologues of chlorobenzene - Andrejeva, Anna; Tuttle, William D.; Harris, Joe P.; Wright, Timothy G. (American Institute of Physics, 2015)
We report vibrationally resolved spectra of the S1 ← S0 transition of chlorobenzene using resonance-enhanced multiphoton ionization spectroscopy. We study chlorobenzene-h5 as well as its perdeuterated isotopologue, chlorobenzene-d5. Changes in the form of the vibrational modes between the isotopologues and also between the S0 and S1 electronic states are discussed for each species. Vibrational bands are assigned utilizing quantum chemical calculations, previous experimental results, and isotopic shifts, including those between the 35Cl and 37Cl isotopologues. Previous work and assignments of the S1 spectra are discussed. Additionally, the vibrations in the ground state cation, D+0, are considered, since these have also been used by previous workers in assigning the excited neutral state spectra.